1988
DOI: 10.1111/j.1471-4159.1988.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans in Cortical Autopsy Samples from Alzheimer Brain

Abstract: Each of the known classes of mammalian glycosaminoglycans, with the exception of keratan sulphate, was found in cerebral cortex samples from patients with Alzheimer-type dementia and age-matched controls. These molecules were quantitated, after electrophoresis and staining with Alcian Blue dye, by scanning densitometry. No significant differences were found between the mean levels of each of the above glycosaminoglycans in frontal cortex from patients with dementia compared with controls. An increase (26%; p l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…However, in contrast to persisting levels of ECM proteins and hyaluronan in PNs, hyaluronan is enriched in the coronal and marginal zones of the amyloid plaques. This is in concordance with biochemical investigations showing an increase of hyaluronan up to 26% in the temporal lobe of AD patients (50). The focal elevation of hyaluronan concentration may be related to reactive astrocytes in the surrounding tissue, as the hyaluronan receptor CD44 is located at radially oriented astrocytic processes massively penetrating these plaque territories (3).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, in contrast to persisting levels of ECM proteins and hyaluronan in PNs, hyaluronan is enriched in the coronal and marginal zones of the amyloid plaques. This is in concordance with biochemical investigations showing an increase of hyaluronan up to 26% in the temporal lobe of AD patients (50). The focal elevation of hyaluronan concentration may be related to reactive astrocytes in the surrounding tissue, as the hyaluronan receptor CD44 is located at radially oriented astrocytic processes massively penetrating these plaque territories (3).…”
Section: Discussionsupporting
confidence: 86%
“…Despite advanced stages of amyloid and tau pathology, PNs and ACs, two widely distributed structural phenotypes of condensed ECM were virtually unchanged. This is in agreement with our previous work in human APP transgenic Tg2576 mice showing advanced cortical amyloid plaque pathology (69) and with biochemical data (50).…”
Section: Area-specific Laminar Distribution Patterns Of Pns and Perissupporting
confidence: 93%
“…Another candidate for the endogenous ligand that activates TLR4 in neurons in response to Aβ or HNE mediated toxic conditions is hyaluronan fragments. Levels of hyaluronate were reported to be increased in the temporal cortex of AD patients compared to age-matched control subjects (Jenkins and Bachelard, 1988). Hyaluronases are activated in injured neural tissue resulting in the generation of hyaluronan fragments (Al 'Qteishat et al, 2006) that have been reported capable of activating TLR2 and TLR4 in immune cells (Termeer et al, 2002;Jiang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One study utilizing electrophoretic separation of glycosaminoglycans indicated a moderate increase in HA concentration in 30 month-old rat brain tissue compared to tissues from younger animals (Jenkins and Bachelard, 1988a). HA is similarly elevated in brains from patients with Alzheimer’s disease (Jenkins and Bachelard, 1988b; Suzuki et al, 1965). Whether HA similarly accumulates in the primate brain with normative aging has not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%